Tuning interfacial microstructure of alginate-based amphiphile by dynamic bonding for stabilizing Pickering emulsion. (15th June 2023) - Huang, Shuntian; Wang, Zhaojun; Zhou, Qichang; Yang, Shujuan; Huang, Riting; Mai, Keyang; Qin, Wenqi; Huang, Junhao; Yu, Gaobo; Feng, Yuhong; Li, Jiacheng
Abstract: Polysaccharide-based soft colloidal particles mediated by the dynamic bonding-engineered interfacial self-assembly can regulate the properties of oil-water interfacial films, availing the stability of emulsions under a wide pH range. The amphiphilic phenylboronic alginate soft colloidal particles (Alg-PBA) were designed to stabilize pH-responsive Pickering emulsions (PEs). Combining stability analysis with quartz crystal microbalance and dissipation monitoring (QCM-D), the microstructure and viscoelasticity of Alg-PBA at the oil-water interface were determined. The results showed that PEs stabilized by Alg-PBA due to a thicker and stronger viscoelastic interface film induced by BO bonds and hydrogen bonds. The structure-function relationship of the Alg-PBA emulsifier driven by dynamic bonds was further elaborated at multiple scales by laser scanning microscopy (CLSM) and scanning electron microscopy (SEM). Meanwhile, the microstructure of aerogels templated by emulsion could be tuned by adjusting dynamic bonds, which provides a new idea for polysaccharide soft material engineering. Graphical abstract: Unlabelled Image Highlights: Amphiphilic phenylboronic alginate was used to design Pickering emulsions. Pickering emulsion stability was influenced by interfacial microstructure. Interfacial microstructure engineered by dynamic bonding was regulated. The dynamical bonding emulsion soft template controlled aerogel microstructure.